The Impact of Human Rights Principles on the Criminal Act of Caning: Asymmetric Decentralization Insight - Prasetyo, Dedy Ardian; Rahimah Embong (Lembaga Contrarius Indonesia, 2025)
The implementation of caning punishment in Aceh highlights the challenges of balancing regional autonomy with national and international human rights obligations. This study examines the extent to which human rights principles influence the execution of caning punishment within an asymmetric decentralized system. Using a normative juridical methodology, the research incorporates conceptual, legislative, and comparative approaches. A key comparison is drawn between the implementation of caning in Aceh, Indonesia, and Malaysia, where sharia law also informs the legal system. The findings reveal that caning in Aceh is often excessive, discriminatory, and perpetuates a culture of violence. Unlike Malaysia, where caning is conducted privately within prison facilities to protect the dignity of the accused, Aceh carries out the punishment publicly, emphasizing deterrence and transparency. The study underscores the need for reform, including stricter oversight, alternative rehabilitative punishments such as social work or legal education, and enhanced public and legal awareness of the balance between sharia law and human rights. By adopting a more regulated approach, Aceh can uphold its cultural and religious identity while aligning with human rights standards, ultimately improving Indonesia’s international reputation and fostering a more just and humane legal system.